Comparative analysis of quality of life of HIV positive support group and non-support group members in a tertiary hospital in Anambra State, Nigeria - Okonkwo, Adaeze O.; Uzochukwu, Benjamin S. C.; Nnebue, Chinomnso C. (International Journal Of Community Medicine And Public Health, 2020)
Background: Peer support as a component of chronic disease management strategy is fast gaining prominence especially in resource poor settings. It is apt to X-ray the effects if any, of support group memberships on the quality of life (QoL) of HIV positive clients in our clime. This study aims to determine and compare the QoL of HIV positive support group and non-support group members in a tertiary hospital in Anambra state, Nigeria. Methods: This was an institution based comparative study of 482 HIV positive clients selected using a two-stage sampling. Data were collected by interview using WHOQOLHIV-Bref and semi-structured questionnaire, while data were analysed with statistical package for social sciences version 22.0. Chi square, Pearson chi square and t-test were applied as appropriate to determine statistically significant associations between variables. Level of statistical significance was set at p value of <0.05. Results: Differences between the two comparison groups include: duration of HAART treatment (p=0.003), in the physical domain (p=0.043), psychological domain (p≤0.001), and the level of independence domain (p≤0.001). More of support group members had good QoL in the physical domain (p=0.04,), psychological domain (p=0.001), level of independence domain (p≤0.001) and reported satisfaction with their perceived health status (p=0.000). Clients who were members of support group and those that reported high level of satisfaction with their perceived health status in most domains had higher QoL scores. Conclusions: We recommend continued counselling and health education on the effect of participation in support group and positive perception cum positive living on QoL.